The biology of urate - Keenan, Robert T. (Seminars in arthritis and rheumatism, 2020)
Urate is the end-product of the purine metabolism in humans. The dominant source of urate is endogenous purines and the remainder comes through diet. Approximately two thirds of urate is eliminated via the kidney with the rest excreted in the feces. While the transporter BCRP, encoded by ABCG2, has been found to play a role in both the gut and kidney, SLC22A12 and SLC2A9 encoding URAT1 and GLUT9, respectively, are the two transporters best characterized. Only 8–12% of the filtered urate is excreted by the kidney. Renal elimination of urate depends substantially on specific transporters, including URAT1, GLUT9 and BCRP. Studies that have assessed the biologic effects of urate have produced highly variable results. Although there is a suggestion that urate may have anti-oxidant properties in some circumstances, the majority of evidence indicates that urate is pro-inflammatory. Hyperuricemia can result in the formation of monosodium urate (MSU) crystals that may be recognized as danger signals by the immune system. This immune response results in the activation of the NLRP3 inflammasome and ultimately in the production and release of interleukin-1β, and IL-18, that mediate both inflammation, pyroptotic cell death, and necroinflammation. It has also been demonstrated that soluble urate mediates effects on the kidney to induce hypertension and can induce long term epigenetic reprogramming in myeloid cells to induce “trained immunity.” Together, these sequelae of urate are thought to mediate most of the physiological effects of hyperuricemia and gout, illustrating this biologically active molecule is more than just an “end-product” of purine metabolism.